The extraction of dragon fruit pericarp as colouring agent for painting / Mohd Zamri Azizan - Azizan, Mohd Zamri (Universiti Teknologi MARA, Kedah, 2020)
Dragonfruit pigment is the new colouring agent of this era and proves to be rich in its natural magenta pigment. The strong pigment and high stability has inspired the researcher to come up with a specific test on the credibility of the colours and as an alternative colouring agent to be used on paintings and textiles. The results from this scientific experiment on the pigment proved that it had the strength and stability needed. Although it has not been processed but the role of it being a new colouring agent is as good as synthetic dye that has been established in the market. The specific experiment on artistic test has proved that this pigment also acts as a versatile colouring agent. This could be seen on the compatibility on this pigment and its reaction towards other medias such as canvas, fabric and paper as test on colour stability. As the new colouring agent, it is hoped that the dragonfruit pigment will be given serious consideration as this natural source should be exploited and the uses variated for future use.